Effect of Capitalizing Human Resource Cost on Corporate Profitability in Ondo State, Nigeria - Adewole, Adeyinka Joseph; Ogunyemi, Kayode Joseph; Akinmulegun, Ojo Sunday (International Journal of Shari'ah and Corporate Governance Research, 2019)
The study examined the effects of conventional treatment of Human Asset on Net Profit; determined the effects of Human Resources Capitalization on firm’s net worth; determined the effect of Human Resources Capitalization on firms' share prices. The study adopted the survey research design and well-structured questionnaire was purposively distributed to 100 staffs of selected firms in the Central senatorial district of Ondo state. Data collected were presented and analysed using ANOVA and Regression. The study revealed that creating room for creative accounting, lack of accounting standard backing conventional treatment of human resources and Biasness in financial reporting are joint indicator of the effect of conventional treatment of Human Asset on Net Profit (R2= 0.577; P < 0.005). The study clearly shows that improving investors’ confidence (29.236; 145.171; 0.000), ease in assessing future potential earnings (29.042; 66.933; 0.000); Contribution to decision making process of capital formation (26.197; 100.249; 0.000); sustainable equity position (23.988; 137.766; 0.000); have significant effect on firm’s network. The study also shows that increase in the level of profitability (4.026; 6.789; 0.000), firm’s growth (23.430; 74.008; 0.000); increase in the size of a firm (11.087; 95.832; 0.000); have significantly affected the share price of a firm. It was concluded that increase in profitability, firm size and growth are some of the cogent effect of capitalization of human resources have an effect on the share price of a firm. The study recommends that professionals, regulators and preparers of financial statements should be enlightened in order to improve the reporting of human resources cost on the face of the financial statement.